Madrasah Head of Leadership Style with Performance Teachers - Rosidah Rosidah; Muhammad Dahlan Rabbani; Badruddin H. Subky (Postgraduate Program Magister Pendidikan Agama Islam, 2020)
This study aims to determine the relationship between the leadership style of madrasah principals with the performance of teachers in Madrasah Aliyah Negeri (MAN) 1 Bogor City. The population used is all teachers of the Madrasah Aliyah Negeri (MAN) 1 Bogor City, totalling 43 teachers. This study uses quantitative research methods and questionnaires as instruments. It was then analyzed using correlation and regression analysis, data analysis using Pearson correlation statistical analysis. The results of this study indicate that there is a relationship between the leadership style of madrasa principals with teacher performance calculated with Pearson Correlation, the correlation coefficient value obtained between these variables is 0.690. The coefficient of determination in this analysis obtained a value of 0.475, which means 47.5%. The variable of Teacher Performance can be explained by the Leadership Style. The regression line is Ŷ = 5,100 + 0,912 X. There is a positive Madrasah Head Leadership Style with Teacher Performance. Based on the results of the study it can be said that the leadership style of the madrasah head has a sufficient relationship with the performance of teachers in Madrasah Aliyah Negeri 1 Kota Bogor.Penelitian ini bertujuan untuk mengetahui hubungan gaya kepemimpinan kepala madrasah dengan kinerja guru di Madrasah Aliyah Negeri 1 Kota Bogor. Adapun populasi yang digunakan adalah seluruh guru Madrasah Aliyah Negeri 1 Kota Bogor, yang berjumlah 43 guru. Penelitian ini menggunakan metode penelitian kuantitatif dan kuesioner sebagai instrumen. Kemudian dianalisis menggunakan analisis korelasi dan regresi, analisis data menggunakan analisis statistic Pearson correlation. Hasil penelitian ini menunjukkan bahwa terdapat hubungan antara gaya kepemimpinan kepala madrasah dengan kinerja guru dihitung dengan Pearson Correlation, nilai koefisien korelasi yang diperoleh antara variabel tersebut sebesar 0,690. Nilai koefisien determinasi dalam analisis ini diperoleh nilai 0,475 yang berarti 47,5%. Variabel kinerja Guru dapat dijelaskan oleh variabel Gaya Kepemimpinan. Garis regresi Ŷ = 5,100 + 0,912 X. Ada hubungan yang positif antara gaya Kepemimpinan Kepala Madrasah dengan Kinerja Guru. Berdasarkan hasil penelitian dapat dikatakan bahwa gaya kepemimpinan kepala madrasah memiliki hubungan yang cukup dengan kinerja guru di Madrasah Aliyah Negeri 1 Kota Bogor.